The Discourse of Islamic Education Development Based on Islam Nusantara Concept in IAIN Salatiga - Sahed, Nur; Musari, Musari; Saheed, Nur; Musari (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Islam Nusantara is a type of intrepretations on how to implement Islamic teachings in a contextual basis of reading religious texts. It is aimed to build Umah’s peaceful and harmonious life. Islamic education development based on Islam Nusantara concept which is desired by IAIN Salatiga is an inclusive education on the basis of tolerant values with positive attitudes toward differences as well as heterogeneity, by including Indonesian Islamic education materials and Islam Nusantara values in the courses in IAIN Salatiga. Those values such as tolerant, respecting others, multi culturalism, moderate, hospitable, and peacefulness